Are micelles actually at the interface in micellar casein stabilized foam and emulsions?. (August 2022) - Zhou, Xilong; Yang, Jack; Sala, Guido; Sagis, Leonard M.C.
Abstract: Different casein preparations are used for stabilizing emulsions and foams. For systems made with aqueous micellar casein dispersions, the molecular and colloidal mechanisms responsible for the stabilization of oil-water and air-water interfaces have not been conclusively ascertained. Whether the micelles themselves, small casein aggregates, or individual casein molecules are at the interface is still an open question. Understanding these mechanisms is important for food industries to improve product formulations. We investigated the nonlinear rheology and microstructure of oil-water and air-water interfaces stabilized with casein micelle dispersions and their fractions. Our results convincingly show that the micelles themselves are not adsorbed at the interfaces. For air-water interfaces, the behavior appears to be dominated by β-casein, whereas the properties of oil-water interfaces are dominated by small casein aggregates. These findings are important to understand the stabilization mechanisms of emulsions and foams prepared with caseins or milk. Graphical abstract: Image 1 Highlights: A new approach integrating various analytical techniques is presented. We identify protein species at the O–W or A-W interfaces. Casein micelles cannot adsorb at O–W or A-W interfaces. Small casein aggregates dominate the properties of O–W interfaces. β-casein is the main protein at A-W interfaces.